Alliance Network Position, Embeddedness and Effects on the Carbon Performance of Firms in Emerging Economies. (March 2014) - Ashraf, Naeem; Meschi, Pierre-Xavier; Spencer, Robert
This article explores the effect of network structure on the carbon performance of firms in emerging economies at an ego network level. Building on the theoretical framework of social networks, we posit that an ego firm's network position, structural embeddedness, and structural constraint affect carbon performance. We examine the research hypotheses using a panel data set made up of 44 Indian firms that entered into alliances under the Clean Development Mechanism over the 2005-2009 period. Our main results show that the central position of the focal firm in the network and its degree of network embeddedness exert a positive effect on its carbon performance. This article contributes to the literature on climate strategy by exploring the influence of the structural characteristics of the firm's ego network in the carbon market on its environmental performance.